Council's online disclosure of accountability practices: isomorphism inquiries / Dayang Hafiza Abang Ahmad, Corina Joseph and Roshima Said - Abang Ahmad, Dayang Hafiza; Joseph, Corina; Said, Roshima (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The study aimed to explain the reasons for disclosing the accountability practices information on the Malaysian local councils' websites using the isomorphism tenet. Semi-structured interviews were conducted with officers from 12 selected Malaysian local councils involved in the disclosure of accountability practices on websites. The interviews revealed that the reasons for disclosure of accountability practices information were classified into six themes - regulatory requirements, website administration, community, organisational goals, leadership, and others, which are subsequently linked to the three isomorphism pressures and strategic controls concept. This study demonstrates the effect of the isomorphic influences by local councils on the disclosure of accountability practices on websites. This paper contributes to the public sector accounting research on the use of the isomorphism concept to explain the disclosure of accountability practices on websites and subsequently linked to behavioural control and informational control concepts that are not commonly used in disclosure studies. The findings of this paper are helpful to local councils and policymakers in identifying the reasons for the disclosure of accountability practices on websites, hence, enabling them to improve in the future.